Determinants of Brand Equity (Consumer Base Brand Equity): A Verification Approach on Mobile Sector (Journal of Social Sciences Review, 2023)
Brand equity is an essential concept in marketing, representing the intangible value of an organization's brand. This study focuses on the mobile industry in Punjab, Pakistan, analyzing four determinants of brand equity: brand awareness, brand association, perceived quality, and brand loyalty. Conveniently sampling 350 respondents from major cities in Punjab, with a response rate of 94%, the research establishes four hypotheses. Data analysis, based on 34 items and utilizing Cronbach's alpha coefficient of .854, reveals that brand awareness and brand association have a positive and significant impact on brand equity. However, perceived quality has a negative and significant impact, while brand loyalty has a negative and insignificant impact. Notably, brand awareness emerges as the most influential determinant of brand equity in the mobile sector.
Keywords: Brand Equity; Brand Awareness; Brand Association; Brand Loyalty; Perceived Quality